Beneficial effects of ice ingestion as a precooling strategy on 40-km cycling time-trial performance - Ihsan, M.; Landers, G.; Brearley, M. B.; Peeling, P. (International Journal of Sports Physiology and Performance, 2010)
Purpose: The effect of crushed ice ingestion as a precooling method on 40-km cycling time trial (CTT) performance was investigated. Methods: Seven trained male subjects underwent a familiarization trial and two experimental CTT which were preceded by 30 min of either crushed ice ingestion (ICE) or tap water (CON) consumption amounting to 6.8 g·kg-1 body mass. The CTT required athletes to complete 1200 kJ of work on a wind-braked cycle ergometer. During the CTT, gastrointestinal (Tgi) and skin (Tsk) temperatures, cycling time, power output, heart rate (HR), blood lactate (BLa), ratings of perceived exertion (RPE) and thermal sensation (RPTS) were measured at set intervals of work. Results: Precooling lowered the Tgi after ICE significantly more than CON (36.74 ± 0.67°C vs 37.27 ± 0.24°C, P < .05). This difference remained evident until 200 kJ of work was completed on the bike (37.43 ± 0.42°C vs 37.64 ± 0.21°C). No significant differences existed between conditions at any time point for Tsk, RPE or HR (P > .05). The CTT completion time was 6.5% faster in ICE when compared with CON (ICE: 5011 ± 810 s, CON: 5359 ± 820 s, P < .05). Conclusions: Crushed ice ingestion was effective in lowering Tgi and improving subsequent 40-km cycling time trial performance. The mechanisms for this enhanced exercise performance remain to be clarified.